A wearable, self-adhesive, long-lastingly moist and healable epidermal sensor assembled from conductive MXene nanocomposites. Issue 5 (3rd January 2020) - Wu, Xiaoxuan; Liao, Hui; Ma, Di; Chao, Mingyuan; Wang, Yonggang; Jia, Xiaolong; Wan, Pengbo; Zhang, Liqun
Abstract : MXene nanocomposites exhibit self-healing capability, self-adhesive performance and long-lasting moisture, and can be assembled as epidermal sensors to wirelessly detect human motion. Abstract : Flexible wearable conductive hydrogel-based epidermal sensors have attracted tremendous attention due to their versatile potential applications in soft robotics, personal healthcare monitoring and electronic skins. However, it remains a critical challenge for hydrogel-based epidermal sensors to simultaneously achieve self-healing capability, self-adhesiveness and long-lasting moisture retention for full-scale human motion biomonitoring. Herein, a conductive, self-healing, adhesive and long-lastingly moist MXene nanocomposite organohydrogel is prepared from the conformal coating of the MXene nanosheet network by the polymer networks of dopamine grafted sodium alginate (Alg-DA), phenylboronic acid grafted sodium alginate (Alg-PBA) and polyacrylamide (PAAm) with a glycerol/water binary solvent as the dispersion medium. The obtained MXene nanocomposite organohydrogel exhibits excellent self-healing capability, superior self-adhesive performance and long-lasting moisture retention (10 days). Furthermore, the MXene nanocomposite organohydrogel can be assembled as a wearable epidermal sensor to detect human motion including large deformation (finger bending and wrist bending) and tiny deformation (swallowing, breathing, and pulse) with durable stability. Meanwhile, the assembled epidermal sensor could be employed to monitor human activities wirelessly via connecting a wireless transmitter. This work sheds new light on the development of flexible, self-healing, adhesive and long-lastingly moist epidermal sensors and electronic skins for personalized healthcare monitoring, human–machine interfaces, and artificial intelligence.